An Open Platform for Global Engineering Initiatives: International Knowledge Centre for Engineering Sciences and Technology Under the Auspices of UNESCO - Chen, Zuoning; Liu, Chang; Ma, Yingchen; Zhang, Ye; Fang, Ying (Frontiers in Political Science, 2022)
Open science provides a bright light for global engineering and technology cooperation and promoting global sustainable development. The International Knowledge Centre for Engineering Sciences and Technology (IKCEST), a category II center under the auspices of UNESCO based in Beijing, aims at providing knowledge-based services at a global scale for policy-makers and engineering science and technology professionals in the world, with particular reference to the developing countries. IKCEST has established a platform with data resources and knowledge services at the core, which includes one general platform and several sub-platforms in its prioritized areas such as the disaster risk reduction (DRR), the intelligent city (ICITY), the engineering education (ENGEDU) and the silk road sciences and technology (SRST). Since the platform was put into operation, it has launched 38 knowledge applications (APPs), serving 3.26 million users from 220 countries and regions worldwide, and offered training for more than 18,000 persons from developing countries. In face of the pandemic, IKCEST set up a COVID-19 column which received positive feedback from users across the globe, the introductory video of which was publicized on the UNESCO official website. As a knowledge hub supporting global sustainable development goals (SDGs) and an open platform for global engineering initiatives, IKCEST will spare no efforts to make greater contributions to providing more tailored and valuable knowledge-based services for global users.